A Study on Design Aesthetic Education and Innovation-Driven Teaching from the Perspective of Kansei Engineering — Taking the Course “Intelligent Agricultural Equipment System Design” at Jiangsu University as an Example - Wang, Liwen (Research and Advances in Education, 2025)
Against the strategic backdrop of rural revitalization and building a strong agricultural nation in China, design education urgently needs to respond to the demands of the times by cultivating innovative talents capable of deeply integrating technology, culture, and aesthetics. This paper takes the course “Intelligent Agricultural Equipment System Design” as a practical vehicle, integrating the ternary theories of Kansei Engineering, a new-era “farming-reading” culture, and agricultural intelligent-manufacturing aesthetics to construct a teaching framework connecting user emotions, cultural roots, and technological aesthetics. The core of the course systematically translates the four aesthetic dimensions of “Form, Meaning, Intelligence, and Reflection” into four core competencies that design students should possess: Innovation in Form and CMF, Scene and Narrative Construction, Interaction and System Integration, and Sustainability and Social Responsibility. Through a meticulously designed “Five Questions, Five Answers, One Extension” teaching path, along with diversified methods such as project-based learning, interdisciplinary workshops, and virtual-physical combined field studies, the course achieves an integrated cultivation of aesthetic perception, cultural understanding, value shaping, and innovative ability. This paper elaborates on the course’s theoretical model, instructional design, implementation process, and innovative features, providing a referential paradigm for teaching reform practices that deeply integrate professional education, aesthetic education, and quality education within design-related disciplines.